The governance impact on the Romanian trade flows: An augmented gravity model - Anca Tamaș; Dumitru Miron (Amfiteatru Economic Journal, 2021)
The aim of this paper is to assess the impact of the quality of the Romanian governance process on the trade with EU countries between 2007 and 2018 using an augmented gravity model. The panel data method was used in order to cope with heteroskedasticity. The sample covers 12 years and includes 27 EU partner countries, chosen because Romania traded with all of them, therefore the zero problem was naturally solved. EViews 10 was used for regression. Cross-section SUR option was used. The six governance indicators were used: voice and accountability, political stability, government effectiveness, regulatory quality, rule of law, control of corruption. The traditional variables (GDP, population, distance, common border, common language) had the expected signs and values. The following governance indicators proved to be significant for exporter countries: control of corruption with a negative influence, government effectiveness and political stability with a positive influence, Romanian political stability with a negative impact, Romanian rule of law with negative influence and Romanian regulatory quality with a positive impact, while the other indicators had a negative influence. The voice and accountability is not significant for exporter countries. An increase with 1% of the values of the government indicators would lead to significant increases of Romanian exports. The greatest impact on the exports would be the improvement of Romanian regulatory quality. The low quality of the Romanian institutions proved to be a major barrier in trading with EU countries. Therefore, an improvement of the Romanian institutions would unleash the trade between Romania and the other EU countries.
Keywords: F14; H11; 330; economic governance; gravity model; governance indicators; trade flows